GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 19430 species occurrences available in GBIF matching the query: Country: Japan Year: 1960-1969 License: CC0 1.0. The dataset includes 19430 records from 100 constituent datasets: 23 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 47 records from Naturalis Biodiversity Center (NL) - Crustacea. 2 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 34 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 1330 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 538 records from Phanerogamic Botanical Collections (S). 4 records from MVZ Herp Collection (Arctos). 1 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 1 records from MVZ Mammal Collection (Arctos). 2 records from LACM Entomology Collection. 4 records from Zoology (Museum of Evolution - Uppsala). 12 records from NPL collections. 18 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 2 records from Lyman Entomological Museum (LEMQ). 1 records from Global compendium of Aedes albopictus occurrence. 1 records from CUMV Fish Collection (Arctos). 3 records from Field Museum of Natural History (Zoology) Bird Collection. 176 records from BMSM Bailey-Matthews National Shell Museum. 99 records from CAS Invertebrate Zoology (IZ). 916 records from EOD - eBird Observation Dataset. 40 records from Recent Invertebrates Specimens. 132 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 2 records from University of Lethbridge Herbarium (LEA). 148 records from Invertebrates Collection of the Swedish Museum of Natural History. 15 records from DMNS Marine Invertebrate Collection (Arctos). 3 records from Essig Museum of Entomology. 85 records from CAS Ichthyology (ICH). 11 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 9 records from Naturalis Biodiversity Center (NL) - Diptera. 6 records from UMMZ Mammal Collection. 2737 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 2 records from Natural History Museum Maastricht (NL) - Entomological Collection. 154 records from CM Herps Collection. 1 records from UWBM Herpetology Collection (Arctos). 198 records from MSB Parasite Collection (Arctos). 26 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 58 records from LACM Vertebrate Collection. 538 records from Natural History Museum (London) Collection Specimens. 2 records from Field Museum of Natural History (Botany) Fungi Collection. 3154 records from NMNH Extant Specimen and Observation Records. 6 records from U. S. National Parasite Collection's holdings from Robert L. Rausch. 10 records from UWBM Mammalogy Collection. 5 records from UWFC Ichthyology Collection. 3 records from The AAU Herbarium Database. 1 records from Herps Specimens. 25 records from LSUMZ Herps Collection. 122 records from Michigan State University Herbarium Lichens. 1 records from MSUM Ichthyology and Herpetology Collections. 3026 records from Herbarium of Kitakyushu Museum of Natural History and Human History. 6 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 3 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 2 records from Invertebrate Zoology Division, Yale Peabody Museum. 6 records from Herbarium Berolinense. 20 records from Lichen Herbarium Berlin. 5 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 6 records from Biologiezentrum Linz. 2 records from Naturalis Biodiversity Center (NL) - Aves. 9 records from University of Alberta Museum of Zoology Amphibian and Reptile Collection (UAMZ). 4 records from UCM Amphibian and Reptile Collection (Arctos). 50 records from Field Museum of Natural History (Botany) Bryophyte Collection. 4 records from WFVZ Bird Collections. 10 records from UMMZ Herpetology Collection. 231 records from PSM Vertebrates Collection. 130 records from University of British Columbia Herbarium (UBC) - Algae Collection. 1 records from Sam Mitchel Herbarium of Fungi (Denver Botanic Gardens). 120 records from Mosses (S). 98 records from Entomology Division, Yale Peabody Museum. 3 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 1 records from UAZ Bird Collection. 3 records from AMNH Mammal Collections. 4 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Types. 43 records from Ouellet-Robert entomological collection (QMOR). 142 records from MSB Mammal Collection (Arctos). 233 records from MSB Host Collection (Arctos). 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 15 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 192 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 6 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 3 records from Oregon State Ichthyology Collection. 173 records from Bernice P. Bishop Museum. 1 records from UMMZ Birds Collection. 291 records from Botany (UPS). 900 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Platyhelminthes. 3 records from NMNH Paleobiology Specimen Records. 2 records from University of British Columbia Herbarium (UBC) - Fungi Collection. 186 records from CAS Herpetology (HERP). 17 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 2521 records from The Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Naturalis Biodiversity Center (NL) - Mollusca. 25 records from SDSM Invertebrate Collections. 13 records from MVZ Bird Collection (Arctos). 1 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 16 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 3 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 54 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from CAS Botany (BOT). 106 records from Fungi (S). 15 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences